Health Services During the COVID-19 Pandemic - World Bank (World Bank, Washington, DC, 2021)
This brief has been produced under the World Bank’s Indonesia Coronavirus disease 2019 (COVID-19) observatory, a partnership among multiple global practices at the Bank that aims to generate near-real-time insights on the impact of the pandemic to inform the Government of Indonesia’s policy response to the COVID-19 crisis. This brief describes results from the fourth round of monitoring between November to December 2020.